2016
DOI: 10.1111/jmi.12492
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective potential of curcumin against norepinephrine‐induced cell death: a microscopic study

Abstract: Cardiomyopathy and associated heart failure continues to be one of the most severe complications that threaten a large population. Curcumin, one of the three curcuminoids of the spice turmeric, is very well known for a multitude of health benefits and functions. Norepinephrine (NE), a catecholamine and also a stress hormone may cause the cardiomyocytes to develop increased sensitivity to death with its increasing concentrations. In this study, we investigated the cardioprotective effect of curcumin in NE-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…For instance, curcumin protects against norepinephrine-induced hypertrophic stress and maintains extracellular matrix remodeling by inhibiting the increased collagen content under hypertrophic stress, and suppressing enhanced gelatinase B expression and gelatinolytic activity in H9c2 cardiomyocytes [ 155 ]. It has also been found that curcumin prevents cardiomyocytes from norepinephrine-induced apoptosis and restores their physiological status [ 156 ]. In addition, the administration of curcumin can attenuate the cytotoxicity of hemiscorpius lepturus venom, which damages the mitochondrial respiratory chain and results in ATP depletion, death signaling, and consequent cardiomyocytes apoptosis [ 157 ].…”
Section: Health Benefits Of Curcuminmentioning
confidence: 99%
“…For instance, curcumin protects against norepinephrine-induced hypertrophic stress and maintains extracellular matrix remodeling by inhibiting the increased collagen content under hypertrophic stress, and suppressing enhanced gelatinase B expression and gelatinolytic activity in H9c2 cardiomyocytes [ 155 ]. It has also been found that curcumin prevents cardiomyocytes from norepinephrine-induced apoptosis and restores their physiological status [ 156 ]. In addition, the administration of curcumin can attenuate the cytotoxicity of hemiscorpius lepturus venom, which damages the mitochondrial respiratory chain and results in ATP depletion, death signaling, and consequent cardiomyocytes apoptosis [ 157 ].…”
Section: Health Benefits Of Curcuminmentioning
confidence: 99%
“…Moving to the realm of cardioprotection, Manghani et al (2017) investigated the influence of Cur on cardiomyocyte apoptosis induced by NE. NE, a stress hormone, can contribute to cardiac apoptosis, leading to heart failure.…”
Section: Therapeutic Potential Of Curcumin In Endocrine Disorders: a ...mentioning
confidence: 99%
“…The study demonstrated that Cur plays a crucial role in safeguarding cardiomyocytes against NE‐induced apoptosis, providing insights into its potential application in preventing cardiac cell death and modulating apoptosis. The implications of Cur in cardiac health add another layer to its multifaceted therapeutic potential (Manghani et al, 2017). The study of Wang et al (2021) delved into the impact of Cur on glioma progression induced by adverse psychological stress.…”
Section: Therapeutic Potential Of Curcumin In Endocrine Disorders: a ...mentioning
confidence: 99%